The Effect of Capital Structure, Operational Efficiency, and Firm Size on Profitability: Evidence from Transportation and Logistics Companies Listed on the Indonesia Stock Exchange (2022-2024) - Devi Dian Syahputri S; Syahrial Hasanuddin Pohan; Maya Macia Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of capital structure, operational efficiency, and firm size on profitability in transportation and logistics companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach was employed using secondary data from audited annual financial reports. The sample was selected through purposive sampling from 30 companies that met the criteria of data completeness and continuous BEI listing, resulting in 90 observations over three years. Analysis was conducted using panel data regression and classical assumption tests with Eviews 12. The results indicate that capital structure (DER) and operational efficiency (TAT) do not significantly affect profitability (ROA), whereas firm size (Ln Total Assets) has a negative and significant effect on ROA. Collectively, all three variables significantly influence profitability, with the model’s explanatory power reaching 87.31%. The study is limited by its relatively short observation period and the use of a single proxy for operational efficiency. This research contributes to corporate finance literature in the transportation-logistics sector and can serve as a reference for management and investors in strategic decision-making and company performance assessment.